2006
DOI: 10.1021/np060071x
|View full text |Cite
|
Sign up to set email alerts
|

Botcinins E and F and Botcinolide from Botrytis cinerea and Structural Revision of Botcinolides

Abstract: Botcinins E and F were isolated together with the known botcinolide. The structures of botcinins E and F were determined to be 3-O-deacetylbotcinin A (5) and 3-O-deacetyl-2-epi-botcinin A (6), respectively, by spectroscopic methods and chemical conversion. The structure of botcinolide was revised on the basis of spectroscopic data and chemical conversion. Botcinolide was originally reported as a nine-membered lactone (7), but the revised structure is the seco acid of botcinin E (13). Thus botcinolide is rename… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 18 publications
3
55
0
3
Order By: Relevance
“…80 A homologue of botcinolide, called homobotcinolide (121a), was isolated by these authors in 1996. 81 The isolation of other botcinolide derivatives was also reported by Collado et al 82,83 Tani et al 84 reinvestigated the spectroscopic data reported for botcinolide and some derivatives, and revised their structures (Figure 1). They found that botcinolide, originally reported as the ninemembered lactone 120a, is in fact the seco acid of botnicin E, as well as the structure of 2-epibotcinolide (122a) was revised as being the same as that of botcinin E (122b).…”
Section: Revised Structuresmentioning
confidence: 66%
“…80 A homologue of botcinolide, called homobotcinolide (121a), was isolated by these authors in 1996. 81 The isolation of other botcinolide derivatives was also reported by Collado et al 82,83 Tani et al 84 reinvestigated the spectroscopic data reported for botcinolide and some derivatives, and revised their structures (Figure 1). They found that botcinolide, originally reported as the ninemembered lactone 120a, is in fact the seco acid of botnicin E, as well as the structure of 2-epibotcinolide (122a) was revised as being the same as that of botcinin E (122b).…”
Section: Revised Structuresmentioning
confidence: 66%
“…The structures of previously known 1, 1a and 2 (Figure 1) were elucidated by analysis of NMR and MS data, together with comparison of their spectral data with those in the literature. [8][9][10] In the course of biological and chemical studies of these compounds, the instability of botcinin A (1) in methanol solution was …”
mentioning
confidence: 99%
“…The structures of previously known 1, 1a and 2 ( Figure 1) were elucidated by analysis of NMR and MS data, together with comparison of their spectral data with those in the literature. [8][9][10] In the course of biological and chemical studies of these compounds, the instability of botcinin A (1) in methanol solution was recognized, and the transformation of compound 1 was monitored in methanol over several days at room temperature by HPLC analysis (Supplementary Information). In this analysis, compound 1 was shown to be slowly converted to previously known 3-O-acetylbotcinic acid methyl ester (1a) and botcinin D (1b), which were identified upon isolation and subsequent structural analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Na infecção acometida por este fungo necrotrófico, a planta hospedeira é bombardeada por numerosas enzimas extracelulares e metabólitos secundários, importantes para o fungo durante o processo de infecção, induzindo a clorose e/ou rompimento da parede celular (COLMENARES et al, 2002;ELAD et al, 2004;CHOQUER et al, 2007 (FEHLHABER et al, 1974;BREITMAIER, 1979;COLMENARES et al, 2002;TANI et al, 2005TANI et al, , 2006REINO et al, 2006;MORAGA et al, 2011). Durante doze dias foi realizado o acompanhamento da produção de sesquiterpenos da classe dos aristoloquenos nos extratos obtidos da biomassa micelial e do líquido fermentado.…”
Section: Capítulo I -Conclusões 168unclassified